2016
DOI: 10.1371/journal.pone.0164709
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method for Verifying War Mortality while Estimating Iraqi Deaths for the Iran-Iraq War through Operation Desert Storm (1980-1993)

Abstract: ObjectivesWe estimated war-related Iraqi mortality for the period 1980 through 1993.MethodTo test our hypothesis that deaths reported by siblings (even dating back several decades) would correspond with war events, we compared sibling mortality reports with the frequency of independent news reports about violent historic events. We used data from a survey of 4,287 adults in 2000 Iraqi households conducted in 2011. Interviewees reported on the status of their 24,759 siblings. Death rates were applied to populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Armed conflicts are a major cause of mortality, injury and disability, imposing heavy burdens on populations, governments, economies, and health care systems worldwide [23,24]. Documentation of the impact of armed conflict on health is one of the most difficult and most important public health challenges [25]. Injuries and fatalities related directly to the Libyan conflict pose a major challenge to the health care services of the country, in which the already fragile infrastructure has been largely disrupted.…”
Section: Discussionmentioning
confidence: 99%
“…Armed conflicts are a major cause of mortality, injury and disability, imposing heavy burdens on populations, governments, economies, and health care systems worldwide [23,24]. Documentation of the impact of armed conflict on health is one of the most difficult and most important public health challenges [25]. Injuries and fatalities related directly to the Libyan conflict pose a major challenge to the health care services of the country, in which the already fragile infrastructure has been largely disrupted.…”
Section: Discussionmentioning
confidence: 99%
“…Although a generalization, it is true that war is always seen as having something to do with a rise in mortality. Several studies have demonstrated an association between war and mortality in other settings [16][17][18] . For example, Li et al 18 , found that deaths during war intervals are significantly higher when compared with peace periods.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated an association between war and mortality in other settings [16][17][18] . For example, Li et al 18 , found that deaths during war intervals are significantly higher when compared with peace periods. Furthermore, previous studies evaluating the impact of peace on health have observed consistent results on the benefits of peace implementation on the improvement of the health of populations 19,20 .…”
Section: Discussionmentioning
confidence: 99%